Alterations in plasma vascular endothelial growth factor levels in patients with schizophrenia before and after treatment. Issue 1 (30th July 2015) - Lee, Bun-Hee; Hong, Jin-Pyo; Hwang, Jung-A; Ham, Byung-Joo; Na, Kyoung-Sae; Kim, Won-Joong; Trigo, Jose; Kim, Yong-Ku
Abstract: Vascular endothelial growth factor (VEGF), a potent angiogenetic factor, is a known neurotrophic factor. In this study, we examined plasma levels of VEGF in 50 patients with schizophrenia (SPR) and 50 healthy control subjects. We also explored any changes in plasma VEGF levels after 6-week treatment with antipsychotic agents in patients with schizophrenia. All subjects with schizophrenia were either medication-naïve or medication-free for at least 4 weeks before assessment. Plasma VEGF levels in all subjects were significantly correlated with smoking duration, which was considered to be a significant covariate. Pre-treatment plasma VEGF levels in patients with schizophrenia were significantly lower than those in healthy controls. Post-treatment VEGF levels were significantly increased in patients with schizophrenia. Plasma VEGF levels in patients with schizophrenia did not exhibit significant correlation with the total or subscale scores of the Positive and Negative Syndrome Scale (PANSS) either at baseline or at the end of the 6-week treatment. In conclusion, our findings reveal that plasma VEGF levels before treatment were lower in patients with schizophrenia and that their VEGF levels increased after treatment. Thus, VEGF may have a neuroprotective role in the improvement of schizophrenia or in the treatment effects of antipsychotics. Highlights: Plasma VEGF levels were measured in patients with schizophrenia healthy controls. Pre-treatment VEGF in schizophrenia were significantly lower than those in controls. VEGF levels in schizophrenia were significantly increased after 6-week treatment.